2021
DOI: 10.1136/bmjpo-2021-001049
|View full text |Cite
|
Sign up to set email alerts
|

Staff–pupil SARS-CoV-2 infection pathways in schools in Wales: a population-level linked data approach

Abstract: BackgroundBetter understanding of the role that children and school staff play in the transmission of SARS-CoV-2 is essential to guide policy development on controlling infection while minimising disruption to children’s education and well-being.MethodsOur national e-cohort (n=464531) study used anonymised linked data for pupils, staff and associated households linked via educational settings in Wales. We estimated the odds of testing positive for SARS-CoV-2 infection for staff and pupils over the period Augus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…However, recent evidence indicates that children below the age of 14 appear to have lower susceptibility to infection and display fewer clinical symptoms [ 2 5 ]. Population-level data suggests that whilst transmission risks within school exists, risks are lower compared to within households [ 6 ]. Adults living with young children (0–11 years) during the period after schools reopened encountered no greater risk of COVID-19 infection [ 7 ], and school staff were at no greater risk of COVID-19 infection than other working-age adults [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence indicates that children below the age of 14 appear to have lower susceptibility to infection and display fewer clinical symptoms [ 2 5 ]. Population-level data suggests that whilst transmission risks within school exists, risks are lower compared to within households [ 6 ]. Adults living with young children (0–11 years) during the period after schools reopened encountered no greater risk of COVID-19 infection [ 7 ], and school staff were at no greater risk of COVID-19 infection than other working-age adults [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous research examining transmission in school-aged children found SARS-CoV-2 infections within the household to be the strongest predictor for a subsequent positive SARS-CoV-2 test[34]. Findings in this study that girls are more likely to test positive for SARS-CoV-2 may suggest sex differences between household contact patterns including more repeated, extended contact with household members by girls.…”
Section: Discussionmentioning
confidence: 53%
“…Whether the school environment provided increased opportunities for transmission cannot be confirmed here, but we do observe that the increase in infections for students began in July 2021 -after students finished school for the summer. Other studies that use data in pre-Delta and Omicron periods suggest that school is unlikely to be associated with high rates of transmission 9,11 ; however, there appears to be limited research after this period. Statistics from Euro surveillance show a sharp increase in COVID-19 for school-aged children and their household members from August to October 2021, and theorise this was partially attributed to the Delta variant.…”
Section: Discussionmentioning
confidence: 99%
“…We created a national e-cohort of school students, staff and linked household members (details outlined in Thompson et al. 11 ) for both students and staff in Wales (Figure 1). We used anonymised linked population-scale, individual-level data held within the Secure Anonymised Information Linkage (SAIL) Databank at Swansea University to create the e-cohort at an individual and household level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation